Wake-Up Stroke and Stroke of Unknown Onset: A Critical Review - Wouters, Anke; Lemmens, Robin; Dupont, Patrick; Thijs, Vincent (Frontiers in Neurology, 2014)
Patients who wake up with an ischemic stroke, account for a large number of the total stroke population, due to circadian morning predominance of stroke. Currently, this subset of patients is excluded from revascularization-therapy since no exact time of onset is known. A large group of these patients might be eligible for therapy. In this review, we assessed the current literature about the hypothesis that wake-up strokes occur just prior on awakening and if this subgroup differs in characteristics compared to the overall stroke-population. We looked at the safety and efficacy of thrombolysis and interventional techniques in the group of patients with unknown stroke-onset. We performed a meta-analysis of the diagnostic accuracy of the diffusion-FLAIR mismatch in identifying stroke within 3 and 4.5 hours. The different imaging-selection-criteria that can be used to treat these patients are discussed. Additional research on imaging findings associated with recent stroke and penumbral imaging will eventually lead to a shift from a rigid time-frame based therapy to a tissue-based individualized treatment approach.